Faktor-faktor yang Mempengaruhi Pengguna untuk Mengadopsi Teknologi Komputasi Awan - Angga Permadi Karpriana (Jurnal Akuntansi Keuangan dan Bisnis, 2015)
This study entitled "Factors influencing users to adopt cloud computing technologies" which aims to examine the factors that influence the users in adopting or using cloud computing services. This study focused on variables Safety (Security), Internet Connection Quality (Quality of Internet), Attitude Toward Use (Attitude Towards Using) and also two variables contained in the Technology Acceptance Model (TAM). This study took a sample of users that have used cloud computing in Yogyakarta. Respondent sample was taken using accidental sampling technique, from all questionnaires were scattered a number of 150, which can be returned and processed as many as 116 samples. Tests were performed using the SmartPLS ver 2.0. The six hypotheses were tested in this study, overall hypothesis showed significant results. The hypothesis suggests that the overall variables proposed in this study influence user behavior in using cloud computing services.Keywords: cloud computing, security, quality of internet connection, attitude toward using, techonology acceptance model